Growth of science in activated sludge modelling – a critical bibliometric review - Ahnert, Markus; Krebs, Peter (Water science and technology, 2021)
In this paper, the tool of bibliometric analysis is applied to the field of activated sludge modelling and its suitability as a first step of a literature analysis is assessed. The analysis is applied to the total dataset considered as well as a time-based classification. It can be shown that this tool is very well suited to filtering the relevant authors and publications, thus enabling a subsequent visual review. The methodology presented can also be applied to sub-disciplines or other subject areas. However, the sole use of the multiple statistical and visual tools is critically questioned. Thus, misinterpretations and apparent findings can result from structural problems in the data or parameters used. Not all of the metrics used are suitable for finding relevant publications, but rather for ranking the criteria studied. However, the latter represents the most widespread application of bibliometrics. From the analysis of the keywords, it could be deduced that there has been a temporal shift from fundamental model aspects to detailed questions such as the integration of sorption and adsorption processes or anaerobic digestion. The modelling of biological phosphorus removal has also surprisingly lost a great amount of importance in the scientific literature.